Discovery Pada Pembelajaran SKI Tingkat MI - Arlina; Afifatuh Rahma; Evi Rizky Sari Siregar; Suci Sanfika (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2023)
The implementation of learning in elementary schools aims to develop students' basic abilities in the form of academic abilities, life skills, moral development, strong character building, the ability to work together, and aesthetic development of the world around them. The purpose of this research is to find out how to implement discovery learning in SKI lessons. This research is a qualitative research that is a type of social science research that collects and works with non-numeric data, the Library Research approach is used by researchers in this study. In order to carry out discovery learning on material evidence of Muhammad's prophethood, it is carried out in six steps, namely: 1. Preparation, 2. Problem identification, 3. Data collection, 4. Data processing, 5. Proof, 6. Draw conclusions.